THE USE OF APPROXIMATION MODELS OF DISTRIBUTED OBJECTS FOR SYNTHESIS OF DISTRIBUTED CONTROL SYSTEMS - Maksim Ivanovich Pershin (Современная наука и инновации)
The article discusses the frequency method of synthesis of distributed controllers, wherein a distributed object by a special approximation model is being described.